Stock Status of Blue Swimming Crab (Portunus pelagicus Linnaeus, 1758) in Tiworo Strait Waters, Southeast Sulawesi, Indonesia - Yustika Permatahati Intan Permatahati; Nila Nikmatia Bugis; La Sara; Tezza Fauzan Hasuba Hasuba (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2020)
The blue swimming crab (BSC) fishery in Tiworo Strait has been heavily exploited since two decades ago when its worldwide demand and price was very high. Study on population aspects of this organism in this waters is limited. The aim of present study was to investigate growth patterns, population stock status, and size at first gonad maturity of Portunus pelagicus. One of the main fishing ground of BSC around Tiworo Strait waters is at Bangko and Gala Islands. Samples of BSC were taken monthly using gillnet and collapsible trap. Each sample taken was identified its sex, measured its carapace width, and weighed. Data collected from fishing ground of BSC were analyzed to find out growth patterns, population stock status using spawning potential ratio (SPR) method, and the first gonad maturity (CW50). The results of study showed that growth patterns of BSC male and female following isometric growth patterns (b=0) (P<0.05). It was found out that SPR of BSC from both fishing ground was 22.46% and 23.71%, respectively which indicates that population stock status of BSC in Tiworo strait waters is “moderate level” (SPR > 20%). The size at first gonad maturity (CW50) was attained at carapace width of 9.16 cm for male and 10.16 cm for female. Those imply that BSCs allowed to be caught should be >10 cm.